THE ORIGIN OF HIV AND THE WESTERN PROPAGANDA ON THE CONTINENT OF AFRICA: MYTH VESUS REALITY - Nandes Dickson, Cinjel; Andeline Doosuur; Evans Oluwagbamila, Ayeni (GOMBE JOURNAL OF ADMINISTRATION AND MANAGEMENT (GJAM), 2020)
The Human Immunodeficiency Virus (HIV) is a virus that damages the human immune system by destroying the Cd4cells and exposing the body to other infections. There is a lot of tales on its origin and instead of admitting its real state of veracity; the Western World opted to push its origin on the continent of Africa, capitalizing on the continent’s backwardness and ill-informed nature. This study examines the western propaganda on the origin of HIV and how it is using disinformation to credit its origin on the African continent amidst verifiable facts to the contrary; the public is fed with distorted fact, half-truth and outright fabrication. The study has adopted a combination of methods. First, we relied on secondary data drawn from an array of published and unpublished materials relevant to the study; utilizing journals, conference and seminar papers, internet materials, reports and documentary excerpt and video clips. In interpreting our data, the relationship between the real origin of the virus and the western propaganda on the African continent was established at both theoretical and empirical level. Empirically, we used a qualitative and historical method that was critical and analytical in providing descriptive and historical details and providing clear perspective into our research problem. The study established that the conjecture on Kinshasa (DR-Congo), the Central Africa and West Africa, the chimpanzee shared blood with the Africans and the mutation tales were mere Western fabrication intended to deform and debase the image of the continent attributable to its backwardness, ill-formed nature and high level of ignorance. Recommendations such as: good governance, overhaul in the African educational system, thorough check and scrutiny of western scientist on experimentation in the continent and many more were proffered.